Widow inheritance and HIV prevalence in Bondo District, Kenya: baseline results from a prospective cohort study. - Kawango E Agot; Ann Vander Stoep; Melissa Tracy; Billy A Obare; Elizabeth A Bukusi; Jeckoniah O Ndinya-Achola; Stephen Moses; Noel S Weiss (PLoS ONE, 2010)
Widow Inheritance is a widespread cultural practice in sub-Saharan Africa that has been postulated as contributing to risk of HIV transmission. We present baseline results from a study designed to investigate the association between widow inheritance and HIV acquisition.We performed a cross-sectional analysis of baseline data from a prospective cohort study to investigate if widow inheritance is a risk practice for HIV infection. Study participants were 1,987 widows who were interviewed regarding their inheritance status and sexual behavior profile and tested for HIV. Of these widows, 56.3% were inherited. HIV prevalence, at 63%, was similar among non-inherited and inherited widows. We stratified exposure status by the relationship of the widow to the inheritor and the reason for inheritance, and reexamined the HIV status of four subgroups of inherited women relative to the HIV status of non-inherited women. When adjusting for age and level of formal education, widows who were inherited by non-relatives for sexual ritual were significantly more likely to be infected than widows who were not inherited (OR = 2.07; 95%CI 1.49-2.86); widows who were inherited by relatives for sexual ritual also had elevated odds of HIV infection (OR = 1.34; 95%CI = 1.07-1.70). Widows who were inherited by relatives for companionship were less likely than women who were not inherited to be infected with HIV (OR = 0.85; 95%CI 0.63-1.14).HIV prevalence among inherited widows varied depending upon why and by whom they were inherited. The cohort study will determine the risk for HIV acquisition among the HIV seronegative widows in this sample.